Eine ramessidische Sonnenuhr im Tal der Könige - Bickel, Susanne (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
A vertical sundial, painted on a limestone ostracon, was found in an area of Ramesside workmen’s huts during investigations undertaken by the University of Basel Kings’ Valley Project between tombs KV 29 and KV 61. It turns out to be one of the oldest devices of this kind and one of only a few with a secure provenance. As with all devices of time measuring of this type, the accuracy is relative and depends on the period of the year. The precision of the sundial was, however, perfectly suited to regulate the shifts of the workmen and their recreation breaks.